2010
DOI: 10.1074/jbc.m110.147439
|View full text |Cite
|
Sign up to set email alerts
|

Cystathionine γ-Lyase-deficient Mice Require Dietary Cysteine to Protect against Acute Lethal Myopathy and Oxidative Injury

Abstract: Cysteine is considered a nonessential amino acid in mammals as it is synthesized from methionine via trans-sulfuration. However, premature infants or patients with hepatic failure may require dietary cysteine due to a lack of cystathionine ␥-lyase (CTH), a key trans-sulfuration enzyme. Here, we generated CTH-deficient (Cth ؊/؊ ) mice as an animal model of cystathioninemia/cystathioninuria. Cth ؊/؊ mice developed normally in general but displayed hypercystathioninemia/hyperhomocysteinemia though not hypermethio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
229
2
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 206 publications
(245 citation statements)
references
References 64 publications
6
229
2
2
Order By: Relevance
“…It is therefore interesting that plasma cystathionine demonstrated a positive association with asymmetric dimethylarginine in our study, given that asymmetric dimethylarginine may induce vascular dysfunction through suppression of endothelial nitric oxide synthase 31. In addition, systemic cystathionine elevation has previously been related to impaired downstream catabolism to cysteine, rather than increased production per se 7, 32. Reduced cystathionine‐transsulfuration may impair glutathione production and thereby lead to oxidative stress 7.…”
Section: Discussionmentioning
confidence: 64%
See 4 more Smart Citations
“…It is therefore interesting that plasma cystathionine demonstrated a positive association with asymmetric dimethylarginine in our study, given that asymmetric dimethylarginine may induce vascular dysfunction through suppression of endothelial nitric oxide synthase 31. In addition, systemic cystathionine elevation has previously been related to impaired downstream catabolism to cysteine, rather than increased production per se 7, 32. Reduced cystathionine‐transsulfuration may impair glutathione production and thereby lead to oxidative stress 7.…”
Section: Discussionmentioning
confidence: 64%
“…Oxidative stress can, in turn, further impair endothelial morphology by inactivating nitric oxide,9 in addition to mediating several other biological processes such as lipid peroxidation and induction of vascular lesions 1. Notably, a previous study from a subsample of the current cohort showed that higher plasma cystathionine concentration are related to low levels of reduced glutathione,33 indicating impaired antioxidant defence 7…”
Section: Discussionmentioning
confidence: 79%
See 3 more Smart Citations